Data-Driven Technology for Engineering Systems Health Management Design Approach, Feature Construction, Fault Diagnosis, Prognosis, Fusion and Decisions - Niu, Gang.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book introduces condition-based maintenance (CBM)/data-driven prognostics and health management (PHM) in detail, first explaining the PHM design approach from a systems engineering perspective, then summarizing and elaborating on the data-driven methodology for feature construction, as well as feature-based fault diagnosis and prognosis. The book includes a wealth of illustrations and tables to help explain the algorithms, as well as practical examples showing how to use this tool to solve situations for which analytic solutions are poorly suited. It equips readers to apply the concepts discussed in order to analyze and solve a variety of problems in PHM system design, feature construction, fault diagnosis and prognosis.
Background of Systems Health Management -- Design Approach for Systems Health Management -- Overview of Data-driven PHM -- Data Acquisition and Preprocessing -- Statistic Feature Extraction -- Feature Selection Optimization -- Intelligent Fault Diagnosis Methodology -- Science of Prognostics -- Data Fusion Strategy -- System Support and Logistics.
Keywords: Security systems; Electronic digital computers -- Evaluation; Mathematics; Data mining; Pattern recognition systems; Security Science and Technology; System Performance and Evaluation; Applications of Mathematics; Data Mining and Knowledge Discovery; Automated Pattern Recognition